Beans: feasible practices for mothers of school children. - Rodríguez, Shirley; Murillo, Adriana (Agronomía Mesoamericana, 2004)
Feasible practices with regards to bean purchase, storage, preparation, consumption and preservation for mothers of school children from a Costa Rican urban community were identified in this study. Nineteen ideal practices were defined based on the mothers’ actual practices which were obtained through an initial assessment. These ideal practices were used later on to conduct behavior tests, in order to identify the feasible practices, i.e., those that have a good chance of being adopted by the population. Through the behavior tests, it was determined that out of the proposed ideal practices, eight were feasible to be adopted by the mothers. They considered that these practices were innovative, simplified their daily chores, or provided some kind of health benefit. On the contrary, practices that were more laborious, required previous planning or implied a drastic change in their alimentary habits were the ones that resulted least feasible. This work concluded that the most feasible practices for the population to adopt are those that are not very different from their usual alimentary practices. For this reason, whenever a change is to be made in a group of individuals, the effort must start from their day-to-day habits.